THE EFFECT OF BURNOUT, EMOTIONAL INTELLIGENCE AND EXTROVERT PERSONALITY TYPE ON THE PERFORMANCE OF TEACHERS AT SMPN 1 PAGAI UTARA SELATAN - Sari, Laynita; Simaremare, Triberti; Lusiana, Lusiana (Yayasan Education and Social Center, 2025)
This study aims to see the effect of (1) Burnout on the performance of teachers at SMPN 1 Pagai Utara Selatan. (2) Emotional intelligence on the performance of teachers at SMPN 1 Pagai Utara Selatan. (3) Extrovert personality type on the performance of teachers at SMPN 1 Pagai Utara Selatan. (4) Burnout, emotional intelligence and extrovert personality type have a joint effect on the performance of teachers at SMPN 1 Pagai Utara Selatan. The population in this study were all teachers at SMPN 1 Pagai Utara Selatan totaling 41 people. And the technique in taking this sample used the total sampling technique (overall sample). The results of this study indicate that (1) Burnout has a significant negative effect on the performance of teachers at SMPN 1 Pagai Utara Selatan. (2) Emotional intelligence has a positive effect on the performance of teachers at SMPN 1 Pagai Utara Selatan. (3) Extrovert personality type has a positive effect on the performance of teachers at SMPN 1 Pagai Utara Selatan. (4) Burnout, emotional intelligence and extrovert personality type jointly influence the performance of teachers at SMPN 1 Pagai Utara Selatan.